Nilai-Nilai Budaya Cerita Rakyat Inik Kebayan Pada Masyarakat Dayak Seberuang, Kecamatan Sepauk, Kabupaten Sintang - Yoga, Stephanus; Nadeak, Parlindungan; Syahrani, Agus (CV. ITTC INDONESIA, 2023)
Inik Kebayan folklore is a story that lives in the midst of the Dayak Seburuang community. This story involves three main characters, namely Sekling and Kumang as husband and wife, and Grandmother Kebayan. There is also a side character named Temprung, who is Sekling's brother. In addition, there are several supporting characters who only appear once in the story, such as a woodcutter, a rubber cutter, a man who burns the fields, a rice harvester, a grass puller, a rice pounder, and a person who cooks new rice, which gives Kumang directions about Sekling's whereabouts. Inik Kebayan folklore includes three main cultural elements, namely man's relationship with God, man's relationship with nature, and man's relationship with man. Man's relationship with God is reflected in the piety and devotion shown by Kumang, who faithfully follows the instructions of Nenek Kebayan, a figure who is clearly not human. The relationship between humans and nature is seen in the wise way humans utilize natural resources as a form of gratitude to God. Man's relationship with man in this story is shown through the attitude of helping, harmony, wisdom, and compassion. Throughout the story, Inik Kebayan tells of the cultural values upheld by the Seburuang Dayak community, including piety to God, wisdom in utilizing natural resources, as well as helpfulness, harmony, wisdom, and compassion between people. The story provides a deep understanding of life and the values held by the Seburuang Dayak community.